ISLAMIZING MYSTICISM: Tarekat, Santri, and the Collapse of Syncretism in Suharto's Indonesia - Riansyah, Rhonny; Hermanto, Bambang; Salayan, Irwandra (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This article examines the transformation of Sufi orders (tarekat) in Indonesia during the New Order regime by analyzing the rationalization and bureaucratization of mystical Islam within the logic of the modern state. Using Max Weber’s theory of charismatic authority, Talal Asad’s concept of discursive tradition, and decolonial perspectives from Quijano and Mignolo, this study demonstrates that the relationship between the state and Sufi communities is not merely a process of co-optation, but a complex negotiation of power and knowledge. The cases of TQN Suryalaya and JATMAN show how Sufi leaders strategically institutionalized their networks while maintaining spiritual authority at the grassroots level. While this transformation legitimized Sufism in the eyes of the state and mainstream Muslim society, it also contributed to the erosion of syncretic traditions that had long characterized local Islam. However, through tactics of epistemic delinking, many tarekat retained their autonomy, allowing mystical practices to persist beneath the surface of formal religious structures. This study argues that the Islamization of mysticism in Indonesia is not a linear process of purification, but a contested field of tradition, modernity, and resistance. It offers a nuanced understanding of how local religious actors navigate state hegemony while preserving alternative forms of spiritual knowledge.